Analysis of motion detection of breast tumor based on tissue elasticity from B mode ultrasound images using gradient method optical flow algorithm - Shuib F.M.M.; Othman, M.; Abdul Rahim, K.; Zulkifli Z. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus